Exploring Extremozymes: Adaptations, Bioprospecting, Enzyme Engineering and Applications - Alabhai, Jadav Mulji; Manjula, Banavath; Mishra, Harshit; Sangeetha, Jeyabalan (Current Enzyme Inhibition, 2025)
Microorganisms thriving in extreme environments produce extremozymes, which have attracted increased interest due to their extraordinary stability and catalytic competence under various environmental stress conditions. This broad review discusses extremozymes' functional efficiency and structural adaptations, encouraging them to survive in extreme environmental niches. In addition, the article discusses different strategies and methodologies used in the bioprospecting of extremozymes, from their isolation, screening, and characterization to explore them for broader utilization. Extremozymes that can operate under extreme salinity, temperatures, and pH ranges are valuable tools for detecting the evolving problems different industries face. Extremozymes are also of great importance in solving environmental issues. These materials' specific capabilities and properties have contributed to waste management solutions, bioremediation efforts, and the sustainable use of resources. Moreover, extremozymes are very useful in agricultural applications. Enzyme engineering plays a significant role in making extremozymes more effective. Overall, this review will explore the power of extremozymes from basic to sustainable applications and innovation in different fields.
Keywords: industrial applications